An inverse heat transfer method for determination of the workpiece temperature in grinding (Journal of Production Engineering, 2009)
This paper present investigation of the thermal state in grinding process, using inverse heat transfer problems. Based on a temperature measured at any point within a workpiece, this experimental and analytical method allows determination of the maximal temperature on wheel/workpiece interface as well as the complete temperature field in the workpiece surface layer. To solve the inverse heat transfer problems, a numerical method of finite differences in implicit form was chosen.
Keywords: Grinding process; Temperature field; Inverse problems